ANALYSES ON LEGAL SYSTEMATIC ARRANGEMENT AND POLICE STANDARD OPERATING PROCEDURES - D, Erdenebaatar (Shinzhlekh Ukhaany Akadjemijn medee, 2018)
Like any country carries out both foreign and domestic policy management, similarly administration also carries out internal and external operations and manages them with legal norms. From this, the internal administrative operation of the police organization and its legal management is directed towards ensuring the implementation of the law and improving operation results of its personnel and organizations. As the legal act systemization is also directed towards result improvement, hence I propose that it is of importance and demand to study the interconnection between them and utilization of it in practice.The purpose of this study is to show the results and differences from implementing legal techniques in the legal sector and establishment of legislative institutions, viewing legal act systemization technique as the theoretic foundation for systematic creation of the legal norm acts of the police organization’s internal operation rather than the narrow view of it as only legislation